Partial Adjustment or Stale Prices? Implications from Stock Index and Futures Return Autocorrelations - Ahn, Dong-Hyun; Boudoukh, Jacob; Richardson, Matthew; Whitelaw, Robert F. (Review of Financial Studies, 2002)
We investigate the relation between returns on stock indices and their corresponding futures contracts to evaluate potential explanations for the pervasive yet anomalous evidence of positive, short-horizon portfolio autocorrelations. Using a simple theoretical framework, we generate empirical implications for both microstructure and partial adjustment models. The major findings are (i) return autocorrelations of indices are generally positive even though futures contracts have autocorrelations close to zero, and (ii) these autocorrelation differences are maintained under conditions favorable for spot-futures arbitrage and are most prevalent during low-volume periods. These results point toward microstructure-based explanations and away from explanations based on behavioral models.